Advances in the Development of Biomaterials for Endotoxin Adsorption in Sepsis - Yang, Qinbo; Li, Yupei; Tuohuti, Pazilaiti; Qin, Zheng; Zhang, Zhuyun; Zhao, Weifeng; Su, Baihai (Frontiers in Bioengineering and Biotechnology, 2021)
Sepsis, a life-threatening and intractable disease without any specific treatment, is activated by endotoxin. Some attempts at removing endotoxin to treat sepsis from the blood circulation using different hemoperfusion cartridges have been proposed recently, but they have failed to reduce the mortality of severe septic patients. This review summarizes the latest advances in the development of endotoxin adsorbents. In particular, we highlight two critical parameters for endotoxin adsorbents when they are applied in blood purification: the dissociation constant and the maximum adsorption capacity. We also discuss potential challenges and research directions for the future development of endotoxin adsorbents.